Turbulent flow of oil-water emulsions with polymer additives; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Manzhai V. N. Vladimir Nikolaevich (High Technologies in Oil and Gas Development, 2014)
Title screen